The Impact Of The Capital Structure On The Net Profit Of The Traditional Private Banks Listed On The Damascus Stock Exchange (Latakia University Journal - Economic and Legal Sciences Series, 2021)
Reaching an optimal capital structure helps financial institutions reduce costs to a minimum by reaching the optimal capital combination in which risk and return are balanced, which is reflected in achieving the institution’s objectives in maximizing profits.This research aims to study the effect of the capital structure on net profit in the traditional private banks operating in Syria (with the exception of Islamic banks, because of its reliance on the provisions of Islamic Sharia, and not according to the traditional banking foundations),by conducting a statistical analysis using the SPSS program to show the effect of the internal financing structure (property rights) on the net profit on the one hand, and the effect of the structure of internal financing on the one hand. External financing (debts) on the net profit on the other handThe study population included 11 banks, and the years of study ranged between 9-11 years, and the study concluded that there is a direct correlation between internal financing and the net profit of the traditional banks listed on the Damascus Stock Exchange, as well as The impact of external financing on net profit was found, The study recommended the necessity of relying on internal financing (equity) as a major source of financing, as this would improve the net profit of the traditional banks listed on the Damascus Stock Exchange.